STUDY ON SHEAR DEFORMATION AND FAILURE CHARACTERISTICS OF TWO-DIMENSIONAL CELLULAR STRUCTURE - ZHANG ZuWei; ZHANG ChenFan; DENG QingTian; YANG ZhiChun; Ll XinBo; WEN JinPeng (Jixie qiangdu)
Based on theoretical modeling, finite element simulation and experiment, the shear deformation and failure characteristies of two-dimensional cellular structure were studied, along with the influence of geometric parameters on overall anti-shear property. Through finite element simulation, the shear deformation rule was obtained. A frame shear fixture was used in shear test, whose results were compared with the finite element simulation results. The results show that the failure can attribute to tensile failure and shear failure near the nodes of cell walls, and the damage extends gradually from the edge to the inside. The cell size and cell-wall thickness have significant impact on the shear properties of the material, while the thickness and arrangement angles have little impact on shear properties. The anti-shear property of the hexagonal cellular structure is the largest among hexagonal, re-entrant and semi re-entrant cellular structures.